Governance, Integrity, and Transparency : An Important Development Agenda for MENA - Akhtar, Shamshad (World Bank, Washington, DC, 2012)
The cause of good governance, integrity, transparency, and anticorruption is vital for facilitating private sector led growth and development throughout the Middle East and North Africa (MENA) region. There are many different ways in which weak governance can impede development. It compromises the delivery of public goods and services to the citizens, particularly to the poor and the vulnerable. It complicates the task of regulating markets and creating an enabling environment for private-sector led growth. It undermines meritocracy in the public sector, as well as a government's ability to allocate resources efficiently to achieve its desired ends.